Long‐Term Outcomes of Inferior Meatus Augmentation Procedure to Treat Empty Nose Syndrome. (15th May 2021) - Dholakia, Sachi S.; Yang, Angela; Kim, Dayoung; Borchard, Nicole A.; Chang, Michael T.; Khanwalkar, Ashoke; Lechner, Matt; Nayak, Jayakar V.
Abstract : Objectives/Hypothesis: We sought to report the long‐term, symptom‐focused, prospective outcomes in empty nose syndrome (ENS) patients after undergoing inferior meatus augmentation procedure (IMAP) through use of four validated questionnaires: Empty Nose Syndrome 6‐Item Questionnaire (ENS6Q), 22‐item Sino‐Nasal Outcome Test (SNOT‐22), Generalized Anxiety Disorder 7‐Item Scale (GAD‐7), and Patient Health Questionnaire‐9 (PHQ‐9). Study Design: Prospective case series. Methods: A single‐center prospective case series was performed for patients diagnosed with ENS who underwent IMAP between July 2017 and February 2020. Diagnosis of ENS was based on the following criteria: 1) reported discomfort with nasal breathing and/or paradoxical nasal obstruction after inferior turbinate reduction, 2) a positive ENS6Q score of at least 11, and 3) a positive cotton test. Questionnaire responses were recorded prior to surgery as well as 1, 3, 6, and 12 months postoperatively. Results: Seventeen eligible patients were included. Mean ENS6Q scores were significantly reduced at all postoperative time points ( p  < .0001, p  < .0001, p  < .0001, p  = .0003). Of the six ENS6Q subdomains, five (suffocation, dryness, sense of diminished airflow, nasal crusting, and nasal burning) were significantly reduced 1‐year postoperatively ( p  < .0001, p  = .0004, p  = .0136, p  = .0114, p  = .0080, respectively). SNOT‐22 scores were significantly reduced at all time points ( p  = .0021, p  = .0227, p  = .0004, and p  = .0025). Of the SNOT‐22 subdomains, the sleep subdomain was significantly reduced 1‐year postoperatively ( p  = .0432). Low baseline GAD‐7 and PHQ‐9 scores were recorded at 7 and 9.4, respectively, and although scores at all postoperative time points were reduced, there was no statistical significance. Conclusion: IMAP via implant of cadaveric rib cartilage provides significant, long‐term improvements in ENS‐specific and general sinonasal symptoms. Level of Evidence: 4 Laryngoscope, 131:E2736–E2741, 2021